Synthesis and Characterization of Gamma-Peptide Foldamers - Reidenbach, Andrew (My University, 2011)
Elucidating folding properties of unnatural amino acids has enabled the start of function-directed design. Two types of gamma-amino acids are probed for their abilities to fold into helical secondary structure. Both gamma-amino acids have backbone constraints that arise from a cyclohexane or cyclopentane respectively. The cyclohexyl monomer with and N-terminal Boc-protected gabapentin residue adopts a 14-helical structure in solution when extended beyond a trimer while an alpha/-oligomer of the cyclopentyl constrained gamma-amino acid has not yet been show to adopt any helical folds from 2D-NMR experiments. Collaboration with the Timothy Zwier group at Purdue University has led to preliminary conclusions about the energetic contributions of amide stacking in gamma-amino acids.
14 p.
Keywords: Chemistry; Biochemistry